Influence of Climate Variability on the Livelihoods of Rural Women in Bungoma County, Kenya - Barasa, Nancy Wanjala; Agwata, Jones F.; Kibugi, Robert (Machakos University Press, 2021)
Women face various challenges due to climate variability which affects their livelihoods at various geographical levels. This is due to their social roles and gender inequalities they face in terms of their access to and control of resources and their low participation in decision-making. To adequately address the challenges faced it is necessary to assess the impact of climate variability on the livelihoods of rural women at the County level. This study assessed the influence of climate change on the livelihoods of rural women in Bungoma County. The study used a descriptive study design to assess the impact of climate variability on the livelihoods of the women in the County. Both primary and secondary data were obtained through qualitative and quantitative means. Rainfall and temperature data were obtained from the Kenya Meteorological Department while data on livelihoods was obtained from the women through questionnaires using random sampling technique and Focused Group Discussions. Data was analysed using the SPSS statistical software. Results indicated that rainfall and temperature varied from year to year leading to occurrence of droughts and floods whilst the distribution of livelihood assets of the women in the County was heavily influenced by drought and seasonal flood occurrence in the County. It is recommended that there should be concerted efforts by the County government to create awareness on how climate change affects the women’s livelihoods to enable them cope well with the negative consequences on the livelihoods.
Keywords: Climate Change; Livelihoods; Rural Women